2015
DOI: 10.1371/journal.pone.0125056
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Novel Mechanism of Antimicrobial Action of a Cyclic R-,W-Rich Hexapeptide

Abstract: The development of antimicrobial peptides as new class of antibiotic agents requires structural characterisation and understanding of their diverse mechanisms of action. As the cyclic hexapeptide cWFW (cyclo(RRRWFW)) does not exert its rapid cell killing activity by membrane permeabilisation, in this study we investigated alternative mechanisms of action, such as peptide translocation into the cytoplasm and peptide interaction with components of the phospholipid matrix of the bacterial membrane. Using fluoresc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 59 publications
4
48
0
Order By: Relevance
“…In agreement with the cytoplasmic membrane as the likely cellular target6, cWFW elicited a typical cell envelope stress response characterised by upregulation of proteins controlled by the extracytoplasmic function (ECF) sigma factors SigM, SigW and SigX (Table 1). In addition, marker proteins indicative of membrane damage (phage shock protein PspA and NAD synthase NadE) and impairment of membrane-bound steps of cell wall synthesis (PspA homologue LiaH and the Sigma M-controlled protein YpuA) were upregulated.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…In agreement with the cytoplasmic membrane as the likely cellular target6, cWFW elicited a typical cell envelope stress response characterised by upregulation of proteins controlled by the extracytoplasmic function (ECF) sigma factors SigM, SigW and SigX (Table 1). In addition, marker proteins indicative of membrane damage (phage shock protein PspA and NAD synthase NadE) and impairment of membrane-bound steps of cell wall synthesis (PspA homologue LiaH and the Sigma M-controlled protein YpuA) were upregulated.…”
Section: Resultsmentioning
confidence: 86%
“…Earlier investigations have suggested that cWFW does not permeabilize the cytoplasmic membrane of E. coli , or form pores in model membranes56. However, the induction of the general SigB-dependent stress response and the similarity of the proteomic response triggered by MP196 and gramicidin S suggests that cWFW might nevertheless cause energy starvation linked to membrane depolarisation in B. subtilis .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Dathe lab has carried out a series of studies of cyclic hexapeptide interactions with single, live E. coli and B. subtilis cells [24]. These peptides are attractive drug candidates due to their resistance to proteolysis.…”
Section: Survey Of Recent Spatiotemporal Studiesmentioning
confidence: 99%
“…In early work, a standard assay using the β-galactosidase substrate ONPG showed that lethal dosages of c -WFW never permeabilize the CM of E. coli . A recent imaging study using an analogue labeled with the fluorescent dye NBD (4-chloro-7-nitrobenzofurazan), called c -W(NBD)W (Figure 3) found strong accumulation of the peptide at the CM and no evidence that the peptide ever accesses the bulk of the cytoplasm [24]. In B. subtilis , both c -W(NBD)W (Figure 3) and the CL stain NAO showed similar patterns, a thin staining of the CM plus strong accumulation at the septal and polar regions.…”
Section: Survey Of Recent Spatiotemporal Studiesmentioning
confidence: 99%